Organo-protective effects of quinapril: pharmacogenetic aspects - D. A. Sychev; O. V. Muslimova (Кардиоваскулярная терапия и профилактика, 2011)
The review presents current experimental and clinical evidence on organo-protective effects of an ACE inhibitor quinapril. These effects are dependent on I/D polymorphism of ACE gene. The data available are consistent that quinapril could modulate this genetic risk factor, highly prevalent in Russian patients.